The Determination of Lower Limit Detection of X-Ray Fluorescence for Zinc Powder Suspended in Engine Oil - Sarkiss, Zareh A. (Iraqi Journal of Physics, 2008)
In this work Different weight of pure Zinc powder suspended particles in 4ml base engine Oil were used. Intensity of Kα Line was measured for the suspended particles ,also for mixture which consist from Zinc particle blended with Engine base Oil. Calibration Curve was drawn between Ikα line Intensity and Zinc concentration at different operation condition. The Lower Limit detection (LLD) and Sensitivity (m) of Spectrometer were determined for different Zinc Concentration (Wt%). The results of LLD and m for Samples were analyzed at Operation Condition of 30KV,17mA is best from Samples were analyzed at Operation Condition of 25KV,15mA